Hubungan Self-Efficacy Terhadap Koping Stres Pada Pasien Kanker Rs Colombia Asia Semarang - Budi Lestari; Dwi Retnaningsih; Menik Kustriyani (Journal of Medical Practice and Research, 2026)
This study examines the relationship between self-efficacy and stress coping strategies among cancer patients at Columbia Asia Hospital Semarang using a quantitative correlational design with a cross-sectional approach. The study involved 30 cancer patients selected through non-probability sampling based on predefined inclusion criteria. Data were collected using validated instruments, namely the General Self-Efficacy Scale (GSE) and Brief COPE Inventory, and analyzed using univariate and Spearman rank correlation tests. The findings indicate that most patients demonstrated moderate levels of self-efficacy and coping strategies, reflecting an ongoing psychological adaptation process to disease-related stressors. A statistically significant and very strong positive correlation (ρ = 0.926; p < 0.05) was identified between self-efficacy and coping strategies, suggesting that higher self-efficacy is associated with more adaptive coping mechanisms. These results highlight the critical role of self-efficacy as a psychological determinant in managing stress among cancer patients. The study underscores the need for integrating psychosocial interventions into oncology care to enhance patients’ adaptive capacity, improve treatment adherence, and promote overall well-being.